Patho-Mechanisms for Hemorrhage/Sepsis-Induced Indirect Acute Respiratory Distress Syndrome: A Role for Lung TIE1 and Its Regulation by Neutrophils. Issue 4 (14th April 2022) - Zhu, Jiali; Li, Jinbao; Chung, Chun-Shiang; Lomas-Neira, Joanne L.; Ayala, Alfred
ABSTRACT: Introduction: Severe hemorrhage (Hem) has been shown to be causal for the development of extra-pulmonary/indirect acute respiratory distress syndrome (iARDS) and is associated with severe endothelial cell (EC) injury. EC growth factors, Angiopoietin (Ang)-1 and -2, maintain vascular homeostasis via tightly regulated competitive interaction with the tyrosine kinase receptor, Tie2, expressed on ECs. Objective: Since it has been reported that the orphan receptor, Tie1, may be able to play a role in Ang:Tie2 signaling; we chose to examine Tie1's capacity to alter the lung Ang:Tie2 interaction in response to the sequential insults of shock/sepsis (cecal ligation and puncture [CLP]), culminating in iARDS. Methods: Male mice were subjected to Hem alone or sequential Hem followed 24 hours later by CLP that induces iARDS. Changes in lung and/or plasma levels of Tie1, Tie2, Ang-1, Ang-2, various systemic cytokine/chemokines and indices of lung injury/inflammation were then determined. The role of Tie1 was established by intravenous administration of Tie1 specific or control siRNA at 1 h post-Hem. Alternatively, the contribution of neutrophils was assessed by pre-treating mice with anti-neutrophil antibody depletion 48 h prior to Hem. Results: Lung tissue levels of Tie1 expression elevated over the first 6 to 24 h post-Hem alone. Subsequently, we found that treatment of Hem/CLP mice with Tie1-specific siRNA not only decreased Tie1 expression in lung tissue compared to control siRNA, but, suppressed the rise in lung inflammatory cytokines, lung MPO and the rise in lung protein leak. Finally, much as we have previously shown that neutrophil interaction with resident pulmonary vascular ECs contribute significantly to Ang-2 release and EC dysfunction, central to the development of iARDS. Here, we report that depletion of neutrophils also decreased lung tissue Tie1 expression and increased Tie2 activation in Hem/CLP mice. Conclusion: Together, these data imply that shock-induced increased expression of Tie1 can contribute to EC activation by inhibiting Ang:Tie2 interaction, culminating in EC dysfunction and the development of iARDS.